THE EFFECT OF SERVANT LEADERSHIP, SELF-AWARENESS, AND COMPETENCE ON ORGANIZATIONAL COMMITMENT AND PERFORMANCE OF EMPLOYEES OF PUBLIC WORKS IN BANGKALAN DISTRICT - hasanah, uswatun; mujanah, siti (Universitas Dr. Soetomo, 2020)
The purpose of this study was to analyze the effect of Servant Leadership, Self-Awareness and Competence on Organizational Commitment and Performance of Employees of Dinas Pekerjaan Umum, Bangkalan State. Indonesia. Sample in this study was 82 Employees of Dinas Pekerjaan Umum, Bangkalan State which gather using the Purposive Sampling technique. Data collection methods used survey techniques with questionnaires as instruments, and data analysis methods used PLS (Partial Least Square). The results of this study indicate that Servant Leadership, Self Awareness, and Competence has a significant effect on Organizational Commitment, Further analysis shows that Servant Leadership has a significant influence on the Performance, but Self Awareness Competence has not significant effect on the Performance, eventhouth Organizational Commitment has significant impact on the Performance, its mean that servant leadership and self awareness has important role on increasing the performance of the employees.